Dietary Advice on Prescription (DAP). A Pedagogical Model for Better Dietary Habits Tested in a Two-Year Randomized Clinical Trial. - Johansson, Gunnar (Journal of Preventive Medicine And Care, 2017)
There Is A Gap Between What We Know And What We Do, Such As Knowing What We Should Eat And What We Actually Eat, A So-Called “Attitude/Behavior Gap”. It Is Not Necessary To Go From A Change In Attitude To A Change In Behavior. It Is Possible To Do The Opposite; In Other Words, It Is Possible To Go From A Change In Behavior To A Change In Attitude. The Objective Of This Paper Is To Describe And Explain The Concept Of Dietary Advice On Prescription (DAP) And Present The Reasons And Evidences For The DAP Messages. Dietary Advice On Prescription (DAP) Starts With Discussing Behaviors Related To Dietary Habits And Then Goes From Behaviors Towards Attitudes. DAP Is A Theory-Based Pedagogical Model That Deals With Behaviors Related To Why, How And When We Eat, Rather Then What We Eat. The DAP Model Is A Method That Quickly Leads The Client Onto A Track That Yields Autonomy, Respects The Client’s Integrity, Gives Confirmation, Emphasizes The Delight And Pleasure Of Eating, Stimulates Discussions And Gives The Client The Initiative In These Discussions. In A Clinical Situation, The Counsellor Lays Out The DAP Postcards On A Table And The Client Picks One Card (Or Several) That Feels Relevant And Interesting For The Client To Discuss. Together They Make An Agenda For The Discussion Such As, For Instance, In What Order To Discuss The DAP Postcards. The Counsellor Asks In An Open Manner With A Motivational Interview (MI) Spirit Why The Client Has Chosen The Particular Card(S). The Client Explains, Elaborates, Turns And Twist About The Choices He/She Has Made. The Results Of The First Published Qualitative Study Of This Two-Year Randomized Controlled Trial Demonstrate That The Participants Found The Concept Valuable.
Keywords: Dietary Advice; Health Education; Dietary Habits; Behavior Change; Randomized Clinical Trial; Pedagogical Model